Safety and immunogenicity of a vaccine for extra-intestinal pathogenic Escherichia coli (ESTELLA): a phase 2 randomised controlled trial. Issue 6 (June 2019) - Frenck, Robert W; Ervin, John; Chu, Laurence; Abbanat, Darren; Spiessens, Bart; Go, Oscar; Haazen, Wouter; van den Dobbelsteen, Germie; Poolman, Jan; Thoelen, Stefan; Ibarra de Palacios, Patricia
Summary: Background: ExPEC4V (JNJ-63871860) is a bioconjugate vaccine, containing O-antigens from Escherichia coli serotypes O1A, O2, O6A, and O25B, developed for the prevention of invasive extra-intestinal pathogenic E coli (ExPEC) disease. We aimed to assess safety, reactogenicity, and immunogenicity of ExPEC4V in healthy adults. Methods: In this phase 2 randomised, double-blind placebo-controlled study, we recruited healthy adults (≥18 years with a body-mass index of 35 kg/m 2 or less) between Nov 16, 2015, and Aug 8, 2017, and randomly assigned them to receive a single dose of ExPEC4V (antigen O1A:O2:O6A:O25B content 4:4:4:4 μg [group 1]; 4:4:4:8 μg [group 2], 8:8:8:8 μg [group 3], 8:8:8:16 μg [group 4], or 16:16:16:16 μg [group 5]) or placebo. The primary objectives were evaluation of the safety, tolerability, and immunogenicity of ExPEC4V and determination of its dose-dependent immunogenicity 15 days after vaccination by ELISA in individuals who had received at least one vaccination dose. Antibody titres and safety evaluation were used to select two ExPEC4V doses for assessment up to day 360. This trial is registered at ClinicalTrials.gov, number NCT02546960 . Findings: Of 848 enrolled participants, 843 (99%) received the ExPEC4V vaccine (757) or placebo (86) and were included in the safety analysis. Of 757 participants vaccinated with ExPEC4V, 222 (29%) had a solicited local adverse event and 325 (43%) had any solicited systemic adverse event, compared with 11 (13%) and 30 (35%) of 86 participants in the control group. Symptoms were mild-to-moderate. The most frequently reported solicited local adverse event was pain or tenderness (205 [27·1%] of 757 in combined ExPEC4V groups) and the most frequently reported solicited systemic adverse event was fatigue (208 [27·6%] of 757). Only 13 (2%) of 843 had a grade 3 event. At day 15, 80% or more of all participants achieved a two times or greater increase in serotype-specific IgG antibodies (except O25B at the lowest dose, 103 [72%] of 144). At day 360, 66% (95% CI 56·47–74·33) of participants in group 2 and 71% (62·13–78·95) of participants in group 4 selected for long-term follow-up maintained a two times or greater increase in serotype-specific antibody compared with baseline. Interpretation: EXPEC4V seemed well tolerated and elicited robust and functional antibody responses across all serotypes, doses, and age groups. For the two dosages evaluated (4:4:4:8 μg and 8:8:8:16 μg), the immune response persisted for 1 year. Funding: Janssen Pharmaceuticals.